Evaluasi Lanskap Agrowisata Desa Colol di Kabupaten Manggarai Timur - Meta Jitro Gege; Irawan Setyabudi; Debora Budiyono (http://arl.faperta.ipb.ac.id/, 2023)
The development of agricultural tourism villages has a positive impact on the agricultural sector and its people. Colol Village was designated by the Regional Government of East Manggarai Regency as an Agrotourism Village because it has good potential in coffee cultivation. This study evaluated tourism activities in Colol Village Agrotourism and problems from various aspects such as biophysical, socio-cultural, ecological, and tourism potential aspects. These problems must be considered to meet the standards or criteria for agrotourism landscape of Colol Village in Indonesia. In general, the problems formulation in this study includes the evaluation of the CololVillage Agrotourism landscape according to the criteria as a tourist place, and respondents’ opinions about Colol Village Agrotourism. The method used the KPI assessment. KPI evaluation includes physical and biophysical aspects, socio-cultural aspects, agrotourism potential, and ecology. The results show that the ecological aspects of the Colol Village Agrotourism area based on an assessment of KPI 50, topographic indicators, soil types, and indicators or hydrological systems with a value of 2 or good. The biophysical aspect in the Colol Village Agrotourism area is based on a KPI assessment of 66.6. Indicators of trees with optimal or maximum size with a score of 3, land productivity with a score of 2, climate with rainfall with a minimum temperature of 65% is very good with a score of 3. Socio-cultural aspects of the community based on KPI assessment with a score of 62.5. Based on indicators of community participation in planning, organizing, and spontaneous movement with a score of 3. The aspect of object and attraction indicator assessment with a score of 81.25 is very good